Ground vibrations from high-speed railways : prediction and mitigation - Krylov, V. V. (ICE Publishing, 2019)
Ground Vibrations from High-Speed Railways brings together leading international research on prediction and remediation of railway-induced ground vibration. It provides a unique general reference source which will help the reader to study the problem from different points of view, and provide answers to numerous theoretical and practical questions.